Analysis of the methodological application for the development of projects of the territory renewal agency – ART (Revista de Investigaciones Universidad del Quindío, 2023)
The methodologies applied to different projects in the world are analyzed in this work whose purpose is the identification of criteria and aspects that can be applied in a proposed methodology for the Territory Renewal Agency-ART, in Colombia. Lessons learned from both successful cases and others that promote a broader review of the approaches and processes applied to projects, allow in this work a methodological proposal, facing the management of those involved, the phases of the projects, a regulatory framework and a welfare and collaborative, whose eventual application in the ART, can generate results of sustainable local development.
Keywords: Methodologies; territory; involved; social impact; prior consultation; governance; projects; sustainable development